Flood syndrome: a rare case of spontaneous rupture of umbilical hernia in a cirrhotic patient. Issue 6 (14th June 2022) - Gorji, Leva; Brown, Jordan
Abstract: Flood syndrome is a rare and potentially fatal complication of long-standing ascites resulting from a spontaneous rupture of an umbilical hernia. We present the case of a 67-year-old male with a medical history of diastolic heart failure, cocaine abuse, hepatitis C and cirrhosis secondary to daily alcohol consumption who presented to the emergency department with spontaneous rupture of an umbilical hernia with continuous, perfuse drainage of ascites from a 3 cm hernia defect. In this case report, we highlight the successful temporizing and definitive management of flood syndrome, as the patient presented to and was temporized a community hospital and was subsequently transferred to a tertiary care center for definitive management.